2017
DOI: 10.1021/acs.orglett.7b00587
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Dilignol Model Compounds and Their Stereodiscrimination Study with a Dye-Decolorizing Peroxidase

Abstract: A 4-step enantioselective approach was developed to synthesize anti (1R, 2S)-1a and (1S, 2R)-1b containing a β-O-4 linkage in good yields. A significant difference was observed for the apparent binding affinities of four stereospecific lignin model compounds with TcDyP by surface plasmon resonance, which was not translated into a significant difference in enzyme activities. The discrepancy may be attributed to the conformational change involving a loop widely present in DyPs upon H2O2 binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…This is further supported by isothermal titration calorimetry (ITC) and surface plasmon resonance (SPR) experiments (data not shown), where ABTS did not show binding to free enzyme except for nonspecific bindings under very high substrate concentrations. Similar results were also obtained in our study of Tc DyP with lignin model compounds . Therefore, unlike some heme peroxidases in which the reducing substrate binds randomly with free enzyme and cmpd I, sequential binding of H 2 O 2 with free enzyme followed by reducing substrate with cmpd I is proposed for DyPs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is further supported by isothermal titration calorimetry (ITC) and surface plasmon resonance (SPR) experiments (data not shown), where ABTS did not show binding to free enzyme except for nonspecific bindings under very high substrate concentrations. Similar results were also obtained in our study of Tc DyP with lignin model compounds . Therefore, unlike some heme peroxidases in which the reducing substrate binds randomly with free enzyme and cmpd I, sequential binding of H 2 O 2 with free enzyme followed by reducing substrate with cmpd I is proposed for DyPs.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were also obtained in our study of Tc DyP with lignin model compounds. 23 Therefore, unlike some heme peroxidases, in which the reducing substrate binds randomly with free enzyme and cmpd I, 67–69 sequential binding of H 2 O 2 with free enzyme followed by reducing substrate with cmpd I is proposed for DyPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] DyPs have been reported to oxidize various types of industrial dyes, particularly anthraquinone derivatives, as well as phenolic and non-phenolic lignin-related model compounds. [5][6][7][8][9] The catalytic activity of DyPs is pH-dependent and optimum pH is required for their maximum action. 11,17 Our previous studies demonstrated that DyP from Bacillus subtilis (BsDyP) could oxidize different synthetic dyes such as malachite green, methyl violet, and reactive black 5, as well as lignin model, compounds like DMP, VA, and guaiacol at acidic pH.…”
Section: Discussionmentioning
confidence: 99%
“…Dye‐decolorizing peroxidases (DyPs) belong to a family of heme‐containing peroxidase enzymes, which are present in both bacteria and fungi 1–4 . DyPs are well known for their ability to oxidize several synthetic dyes like ABTS, Azure B, Malachite green, Methyl violet, Reactive Black 5, and Reactive Blue 19, which indicate that these enzymes can be employed for the bioremediation of dye‐contaminated wastewater 5–8 . Moreover, earlier studies of DyP have demonstrated that it is involved in the degradation of lignin and lignin model compounds such as guaiacol, veratryl alcohol (VA), syringol, syringaldehyde etc., and can be used to oxidize different compounds such as phenols, carotenoids, and aromatic sulfides, suggesting that DyPs act as ligninolytic enzymes 8–12 .…”
Section: Introductionmentioning
confidence: 99%